Antônio Conselheiro: o entrelugar na materialidade discursiva. - Gehlen, Simone Carina (2013)
Grounded in Dedicated to Discourse Analysis of French (AD), this present work aims analyze the effects of meanings produced by the shell-work Os Sertões, of Euclides da Cunha, regarding the character Antônio Conselheiro, being the work in question the corpus of this research. The choice of such a work as corpus is justified by the fact of having acquired great importance to the national literature and be considered a benchmark when it comes to the War of Canudos. The work of Os Sertões, not only gained importance in the field of literature, but also in other areas of knowledge such as history, sociology and anthropology, and is therefore considered a work difficult to classify. This is due to the fact Os Sertões, fiction, having as its theme an episode of national history, bringing the storyline production conditions of the time (the War of Canudos, consolidation of the Republic, the discourse of science deterministic in vogue in Brazil), as well as the hegemonic ideology of the XIX century. In this sense, we are interested by how Euclides da Cunha presents the character Antônio Conselheiro, considering that the discourses related to character, not only show the subject position of Cunha, but the discursive formation of the time, in regard to the episode Canudos and its leader. By means of the choice of some discursive sequences, we intend to present the way the author builds his character, presenting it and assigning it senses concerning madness, mystery, religious fanaticism and violence. Given that the focus of this research centers around the figure of the Conselheiro and, being inspired by a character in real life, to analyze the conditions of production of the work, seek other discourses, produced at the time of the War of Canudos, that could have collaborated in the production of meanings about the Conselheiro in the plot of the work, as, for example, the journalistic discourse wartime, the discourse of science deterministic in vogue in Brazil in the late XIX century, and early XX century and, finally, the political discourse, with a view to consolidating the republican regime installed in Brazil in 1889. In this study, Antônio Conselheiro will be treated as fictional character, built by Euclides da Cunha through verbal resources, in others words, although the Conselheiro of Os Sertões is inspired by the real-life Conselheiro, during the research it will be seen as a fictitious. The proposed analyzes are mediated in accordance with studies Michel Pêcheux (2009 [1988]), Orlandi (2007 till [1999], 2007b [1992]) and Mariani (1998) the main authors give theoretical support to the discussions. Analyze the effects of meaning produced around the work Conselheiro in Os Sertões is, generally, a glance at the processes of signification and it is direct link with the ideology in that way that imposes a given situation are the result the interplay of forces between discursive formations in dispute.